2006
DOI: 10.1161/01.atv.0000233334.24805.62
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Arginase by H2O2Impairs Endothelium-Dependent Nitric Oxide-Mediated Dilation of Coronary Arterioles

Abstract: Objective-Overproduction of reactive oxygen species such as hydrogen peroxide (H 2 O 2 ) has been implicated in various cardiovascular diseases. However, mechanism(s) underlying coronary vascular dysfunction induced by H 2 O 2 is unclear. We studied the effect of H 2 O 2 on dilation of coronary arterioles to endothelium-dependent and endothelium-independent agonists. Methods and Results-Porcine coronary arterioles were isolated and pressurized without flow for in vitro study. All vessels developed basal tone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 67 publications
3
91
0
Order By: Relevance
“…It has been shown that hydrogen peroxide, a downstream product from superoxide dismutase, can impair vasomotor function. 29,46 Inhibition of hydrogen peroxide formation by cell-permeable polyethylene-glycolated catalase has been reported to prevent hydrogen peroxide signaling in the vasculature. 47 To determine whether hydrogen peroxide contributed to the observed vascular dysfunction in our study, the vessels were pretreated with this modified catalase, and the effect of CRP was subsequently investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that hydrogen peroxide, a downstream product from superoxide dismutase, can impair vasomotor function. 29,46 Inhibition of hydrogen peroxide formation by cell-permeable polyethylene-glycolated catalase has been reported to prevent hydrogen peroxide signaling in the vasculature. 47 To determine whether hydrogen peroxide contributed to the observed vascular dysfunction in our study, the vessels were pretreated with this modified catalase, and the effect of CRP was subsequently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of LOX-1 and CD32 in mediating the CRP effect were examined in a separate group of vessels by determining dilation to serotonin before and after coadministration of CRP with an anti-LOX-1 antibody (5 µg/mL; Abcam) 25 or an anti-CD32 antibody (5 µg/mL; Santa Cruz Biotechnology). 26,27 κ-Carrageenan (125 µg/mL), a LOX-1 antagonist, 25,28 and catalase (1000 U/mL), 29,30 the hydrogen peroxide scavenger, were administered to determine the role of LOX-1 and hydrogen peroxide, respectively, in the observed CRP effect. In another cohort of vessels, vasodilation to arachidonic acid (10 µmol/L), 10 an endothelium-dependent PGI 2 -mediated agonist, was examined before and after incubation with PGI 2 synthase inhibitor trans-2-phenyl cyclopropylamine (TPC; 100 µmol/L) 10 or after 60-minute intraluminal incubation with recombinant CRP (7 µg/mL) in the absence or presence of an anti-LOX-1 antibody (5 µg/ mL), TPC plus an anti-LOX-1 antibody, or an anti-CD32 antibody (5 µg/mL).…”
Section: Functional Assessment Of Isolated Coronary Arteriolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cell dysfunction may also involve increased arginase activity, which converts L-arginine to L-ornithine and urea, thus decreasing the substrate for NO production (76). H 2 O 2 upregulates arginase activity and thereby may impair renal vasodilatation (170).…”
Section: Renal Endothelial Cell Dysfunction In Htnmentioning
confidence: 99%
“…Elevated levels of non-heme iron may increase conversion of H 2 O 2 to OH • , contributing to an overall decline in flow-mediated dilation with aging. Furthermore, previous reports have suggested that hydroxyl may contribute to reduced NO-mediated vasodilation (45). We examined flowmediated dilation in the presence of Tempol plus deferoxamine, an iron chelator and inhibitor of OH…”
Section: Sod Dismutates Omentioning
confidence: 99%